EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI,PEMANFAATANSISTEM INFORMASI AKUNTANSI DAN KEPERCAYAAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN: Studi Kasus Karyawan Bagian Akuntansi Unit CD PT.Delta Dunia Tekstil II - Tiyas Yuli Astutik; Shandy Marsono (STIE St. Pignatelli Surakarta, 2020)
Abstract The aim to be achieved from this study is to provide empirical evidence that the effect of the effectiveness of accounting information systems, the use of accounting information systems, accounting information system trust significantly influence employees at PT. Delta DuniaTekstil II. The population in this study were all employees of the administrative staff produced by PT. Delta DuniaTekstil II. The sample of this study was 30 employees of the administration of the production of CD units. The sampling technique used was purposive sampling. The analysis technique consists of classic assumption tests, multiple linear regression analysis, t test, F test, and R. Questionnaires in the Test using Validity Test and Variable Test obtain valid and reliable results. The results of hypothesis testing indicate that the effectiveness of the SIA variable has a positive and significant effect on employee performance variables. The variable utilization of SIA has a positive and significant effect on employee performance variables. The SIA trust variable has a positive and significant effect on employee performance variables. Normality test results show that the assumption of normality, multicollinearity test does not have multicollinearity, heteroscedasticity test there are no variables that occur heteroscedasticity and autocorrelation test does not occur symptoms of autocorrelation. The adjusted R2 value of 82.5% means that the variability of employee performance can be explained by the variable effectiveness of the application of SIA, the use of SIA and the trustworthiness of the SIA while the remaining 17.5% is influenced by other factors outside the variables studied.